ENTREPRENEURIAL INTENTION: MANAGERIAL ABILITY AND CREATIVITY PERSPECTIVE - Kurjono Kurjono; Faqih Samlawi (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2023)
The purpose of this study was to determine the effect of Managerial Ability, and Creativity on the Entrepreneurial Intentions of FPEB students, Universitas Pendidikan Indonesia. The Theory of Planned Behavior is used as a grand theory of intention. The population of this research is FPEB UPI students who have attended entrepreneurship courses as many as 328 students from various study programs at the Faculty of Economics and Business Education (FPEB) Universitas Pendidikan Indonesia. This type of sample uses Proportionate Stratified Random Sampling. Collecting data using a questionnaire. The research instrument was tested for validity and reliability. Data analysis using multiple regression analysis with tools IBM SPSS V.26. The results of the study revealed that each of the independent variables, namely managerial ability, and creativity had an effect on entrepreneurial intentions. It is recommended that the managerial ability variable increase the indicator of accepting the reality of change, the perceived risk creativity variable and the entrepreneurial intention variable, namely the indicator of entrepreneurial readiness.